Avaliação do processo inflamatório pulmonar em murinos infectados pelo Schistosoma mansoni e estimulados com LPS - Ferreira, Amanda Esteves Rocha (2014)
Schistosomiasis, caused by helminth of the genus Schistosoma, is neglected disease in the world and has a high prevalence to be associated with areas where sanitation and hygiene education are insufficient. The disease develop clinical forms in their host vertebrate begins in an acute phase and subsequent development of chronic phase. The chronic phase of the disease causes major damage one of them is the development of lesions in the liver, spleen, intestines and lungs. The portal hypertension caused by disease allows the migration of eggs to the lungs here start a granulomatous inflammatory response. The migration of eggs may favor the displacement set of bacterial infection in a nature. To study the action of bacteria in the organs is common to use the endotoxin wall of Gram-negative bacteria the lipopolysaccharide (LPS). In this study, we evaluated the process pulmonary inflammatory stimulated with LPS in animals infected with Schistosoma mansoni chronic phase. The study groups were divided into Controle/Salina (divided into group Controle/Salalina 6 h (n = 6) and 24 h (n = 6)), Schisto (120 days of infection ( n = 6)), LPS (divided into group 6 h (n = 6) and 24 (n = 6)) and LPS / Schisto(divided in groups 6 h (n = 6) and 24 h (n = 6)). Observed an increase in polymorphonuclear cells (PMNs) in the first 6 hours after inoculation of LPS in group LPS (p<0,001) in relation to the other groups, and the increase (p<0,001) of PMNs in group LPS/Schisto than in groups Controle/Salina and Schisto. After 24 hours inoculation of LPS the process change inflammatory modified with increased cells mononuclerares (MNs) in groups, except in group Controle/Salina(p<0,001). The number of PMNs remained increased in group LPS/Schisto when compared to group Controle/Salina (p< 0,001) and group Schisto (p<0,05). The dosage of nitric oxide concentration increased in group LPS (p<0,001) in relation to the other groups, and group LPS/Schisto (p<0,001) in relation to groups Controle/Salina and Schisto in 6 hours after the LPS inoculation. The pulmonary granulomas did not change significantly in size between groups Schisto and LPS/Schisto This work suggest that schistosomiasis in chronic phase may cause immunosuppression of a Gram- negative bacterial infection concomitant.